The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1123/apaq.29.3.205
|View full text |Cite
|
Sign up to set email alerts
|

Daughters of Mothers With Multiple Sclerosis: Their Experiences of Play

Abstract: A woman who is my unending inspiration of strength and courage. ABSTRACTThis study described the play experiences of daughters who were caregivers to their mothers with multiple sclerosis (MS). The experiences of four CanadianCaucasian women aged 19-26 were captured using phenomenological methods of individual and focus group interviews, field notes, and artefacts. Three themes with supporting sub-themes emerged: (a) being a good daughter, (b) blurred relationship boundaries, and (c) encumbered play. Caregivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 90 publications
1
27
0
Order By: Relevance
“…An interesting finding in our study is the feeling of guilt, which seems related to the relationship parent‐adolescent and the adolescents' perception of themselves as good carers; parallel to Jonzon and Goodwin (). Further, the feeling of shame, that some felt, seems related to their parents appearing different from their peers’ parents and echoes the feeling of guilt, consistent with Horner ().…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…An interesting finding in our study is the feeling of guilt, which seems related to the relationship parent‐adolescent and the adolescents' perception of themselves as good carers; parallel to Jonzon and Goodwin (). Further, the feeling of shame, that some felt, seems related to their parents appearing different from their peers’ parents and echoes the feeling of guilt, consistent with Horner ().…”
Section: Discussionsupporting
confidence: 75%
“…(), and they miss being acknowledged for their contributions, consistent with Turpin et al . (), Jonzon and Goodwin () and Bjorgvinsdottir and Halldorsdottir (). The results of this study further indicate that parents who initiate openness to their adolescents' peers may enhance support offered and thus ease the burden, consistent with Turpin et al .…”
Section: Discussionmentioning
confidence: 99%
“…Young carers express the desire for private spaces that offer them time to relax and be like any other child (Frank, 1995;McAndrew et al, 2012;Metzing & Schnepp, 2008;Moore & McArthur, 2007;Nigel et al, 2003;Phelps, 2012). These private spaces may also include opportunities for young carers' to interact with friends, pursue their hobbies or just have fun (Elf et al, 2011;Jonzon & Goodwin, 2012).…”
Section: E533mentioning
confidence: 99%
“…27, 28 These studies have found that child caregiving demands differ across health conditions necessitating caregiving (e.g., debilitating physical conditions, serious mental health illness, alcoholism). Fears of social service interventions and removal of children from homes prevent some families from seeking formal support services; 7, 10, 12, 25 furthermore, disability can disrupt parental relationships, precipitating divorces and complicating custody decisions.…”
Section: Introductionmentioning
confidence: 99%